Kota Schoemaker: Kota Bandung di Mata Maestro Arsitek H.P. Berlage (1915–1923) - Fadlurrahman, Muhammad Gibran Humam (PURBAWIDYA, 2024)
This article discuss the history of Bandung as a colonial city that was titled 'Schoemaker City' by famous architect H.P. Berlage who visited Bandung in late April 1923. The city of Bandung was being developed rapidly from the 1910s to the early 1920s with the work of well-known Dutch East Indies architects, including C.P. Wolff Schoemaker and Richard L.A. Schoemaker. They designed many public buildings in Bandung with their characteristic architectural styles. This research focuses on the history of Bandung and its image in relation to the architectural works of the Schoemaker brothers during 1915-1923 that impressed H.P. Berlage by using the historical method that consists of heuristics, verification, interpretation, and historiography, as well as the science of architecture. This article analyzes the history of the Schoemaker brothers' architectural works that were prominent in important areas and became part of the activities in Bandung City until titled 'Schoemaker City'. The Schoemaker brothers' architectural designs have a characteristic architectural style and became part of the colonial society's activities in important areas of Bandung City, which encouraged H.P. Berlage to title it 'Schoemaker City'.